Edukasi Perilaku Hidup Sehat Untuk Mencegah Penyalahgunaan Narkoba Di SMAN 1 Kabila - Jasri, Jasri; Biahimo, Moh Ramdan; Haryani, Meri; Irawan, Safri; Alamri, Sakina; Firmansyah, Moh; Djumadi, Moh Rival; Balango, Zulkifli; Triany, Diva; Dumoi, Dzul Fahri Ahmad; Nurudji, Afriyanto; Bakari, Akhmal Halid I; Deluma, Dewiyanyti (-, 2025)
Substance abuse among adolescents is a serious issue that can impact physical, mental, and social health. The drug abuse awareness activity held at SMAN 1 Kabila aimed to raise the awareness of 11th-grade students about the dangers of drugs and the importance of a healthy lifestyle as a preventive measure. This program covered the negative effects of drug abuse on the body and mind, as well as the significance of healthy behaviors, such as balanced nutrition, regular exercise, sufficient sleep, and mental health care. The activity included initial observations, submission of administrative documents, and the implementation of the awareness session through interactive discussions. The evaluation showed that students were able to understand the negative impacts of drugs and were better equipped to face social pressures. It is hoped that this activity can serve as a model for other schools to raise awareness among adolescents to prevent substance abuse.